use FOIL -Firsts, Outside,Insides,Lasts.

then

(2x-2y)(3y+3z)

F = 2x * 3y = 6xy

O = 2x *3z = 6xz

i = - 2y * 3y = 6y^2

L = -2y + 3z = -6yz

so combine em all:

6xy+6xz + 6y^2 -6yz

that's it

FOIL it! Multiply first term, outside terms, inside terms, last terms. Mulitpy the coefficient. So first term is 6xy+.

You can go from there! I know it! :p

if you're suppose to factorise it:

6xy+6xz-6y2-6yz

something like that

(2x-2y)(3y+3z)=

6xy+6xz-6y^2-6yz

use FOIL

6xy+6xz-6y^2-6yz

=6(x-y)(y+z)= 6(xy+xz-y^2-yz)= 6xy+6xz-6(y^2)-6yz

(2x-2y)(3y+3z)

= 6xy + 6xz - 6y^2 - 6yz

- Essay on "How far we are responsible for making ourself ill"?
- Doctor Forms?
- Please help me!?
- Rewrite so subject and verb agree?
- What is an evaluation & a anlysis?
- College Algebra?
- Can any1 help me with this problem? "3x squared -49 = 0"?
- Is it possible to find quintiles in a frequencey data table?i want to learn!!?
- Traditional method of Hypothesis testing?
- Battle of Gettysburg school article!?